CFD Simulation of an Intermediate Temperature, Two-phase Loop Thermosiphon for Use as a Linear Focus Solar Receiver. (May 2017) - Wang, Yinfeng; Wang, Xiaoyuan; Chen, Haijun; Fan, Hongtu; Taylor, Robert A.; Zhu, Yuezhao
Abstract: A horizontal two-phase loop thermosiphon (HLTS) has been developed as a potential receiver for commercial line focusing collectors. The design consists of a horizontal evaporator, an ascending tube (riser), a condenserand a descending tube (downcomer) with U-turn. Dowtherm A, which is suitable for the temperature range of 200∼400 o C was adopted as the working fluid in the HLTS. The heat and mass transfer regimes of the HLTS at different condenser inclination anglesin the heat flux input of 8.5 kW/m 2 were simulated using the VOF model. Theresults show thata liquid seal was formed in the U-turn section which effectively prevents the bidirectional flow in the loop. Nucleate boiling and drop-wise condensation regimes were observed. Different flow phenomena, i.e.stratified fluid flow and drop-wise flow, were found in the horizontal and the inclined condensers, respectively. An inclined angle of 5° was found to effectively improve the heat transfer performance compared with the horizontal model in this study although higher performance could be achieved in higher inclinational angles. Overall, by incorporating all of the salient two-phase mechanisms, this approach enables researchers to optimize the geometric design of a HLTS.